The influence of surface topography on the field emission of nanostructured copper oxide thin films grown by oblique incidence deposition1. Issue 24 (28th June 2015) - Chatterjee, S.; Kumar, M.; Pal, A.; Thakur, I.; Som, T.
<x xml:space="preserve">Abstract</x> The surface morphology dependent field electron emission characteristic of copper oxide thin films shows superior field emission of obliquely sputter deposited thin film (turn-on field ∼1.3 V μm−1) compared to normally deposited film.